IDENTIFIKASI LENGKUAS (Alpinia galanga) SECARA KLT DALAM JAMU PEGAL LINU YANG BEREDAR DI KOTA PINRANG, SULAWESI SELATAN - Nirmayani Abd. Kadir; Amin, asni; Mamat Pratama; A. Amaliah Dahlia (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2025)
Abstract: Jamu pegal linu (tradisional Indonesia medicine) is one of the herbs used to treat aches and pains by the Indonesian people. The galangal is often found in the composition of jamu pegal linu (JPL). The purpose of this study was to identify by TLC the presence of galangal (Alpinia galanga/AG) in JPL from the Pinrang city, Province of South Sulawesi. Methods: Jamu pegal linu that included AG in the label was collected from jamu shops in Pinrang city. Each jamu sample was extracted with 96% ethanol for 24 hours, as well as AG. The extracts were then evaporated until thick. Each viscous extract was analyzed on a plat TLC (thin layer chromatography) plate with a stationary phase of silica gel GF254, and a mobile phase of n-hexan-ethyl acetate (8:2), then detected using UV lamp 254 nm and 366 nm wavelenght, and calculated the Rf (Rate of flow) value. The results showed that herbs A, B, C, D, and E were identified as containing at Rf 0,38; 0,87 dan 0,95 after detection in UV 366 nm, and AG at Rf ..... in UV 254 nm detection. The identification of these herbs can be used as a reference for producers and consumers to confirm the correctness of the composition of AG rhizome in jamu pegal linu.